2022
DOI: 10.1055/s-0042-1748821
|View full text |Cite
|
Sign up to set email alerts
|

Should an Age Cutoff Be Considered for Elective Total Knee Arthroplasty Patients? An Analysis of Operative Success Based on Patient-Reported Outcomes

Abstract: Total knee arthroplasty (TKA) is increasing in the elderly population; however, some patients, family members, and surgeons raise age-related concerns over expected improvement and risks. This study aimed to (1) evaluate the relationship between age and change in patient-reported outcome measures (PROMs); (2) model how many patients would be denied improvements in PROMs if hypothetical age cutoffs were implemented; and (3) assess length of stay (LOS), readmission, reoperation, and mortality per age group. A pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Many of these orthopedic studies have shown obesity and older age, among other risk factors, to be associated with postsurgical readmission. 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Many of these orthopedic studies have shown obesity and older age, among other risk factors, to be associated with postsurgical readmission. 20 , 21 , 22 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, special attention should be paid to high-risk populations, such as obese and elderly patients, who may be denied surgery because of increased complications after arthroplasty. 20,43,44 Using age cutoff values, Bell et al 20 demonstrated that patients older than 80 years experienced more complications; however, most of these patients showed similar improvements in PROMs after TKA compared with their younger counterparts. This illustrates that elderly patients may be denied notable benefits because of withholding TKA based only on their age.…”
Section: Application Of Patient-reported Outcome Measures In Decision...mentioning
confidence: 99%
“…12 PROMs are increasingly being considered as the ideal tool for clinical decision support and shared decision making. 8,16,18-20…”
Section: Introduction: the Importance Of Patient-reported Outcome Mea...mentioning
confidence: 99%
“…Several conditions have been identified in the trauma and elective orthopedic settings to explain the failure of professionals’ and patients’ desired goals, with some authors raising age-related concerns over expected improvement and risks [ 6 ]. Poor nutrition status is a serious issue affecting more than 30% of hospitalized patients [ 7 , 8 ], reducing their quality of life, and hindering postoperative functional rehabilitation and fast discharge [ 9 ].…”
Section: Introductionmentioning
confidence: 99%